Mangrove Land Conversion in Indonesia's Coastal Areas - Apriani, Apriani; Delistiani (Journal of Epidemiology and Health Science, 2026)
Background: Mangrove forests are formations of specific plants, and are generally found growing and developing in protected coastal areas in tropical and subtropical areas. The existence of mangrove forests is very important because it can provide many benefits for human survival, mangrove forests can absorb carbon, prevent sea intrusion, erosion and coastal abrasion, wave dampening, water filtration and become a nursery grown place for several types of animals, especially fish. Objective: This study aims to analyzing land conversion that occurs affects the conversion of mangrove land in coastal areas of Indonesia. Methods: The method used in this study is a literature review study. Literature searches were conducted through the pubmed and google scholar databases using the keyword "mangrove land conversion in Indonesia". Results: Some of the impacts of mangrove land conversion in coastal areas of Indonesia are the formation of ponds and rice fields, settlements, office buildings, fields, ponds and plantations, industrial areas, cultivation ponds, and also conversion into agricultural land such as rice fields and grasslands, accompanied by an increase in demand for palm oil which causes land clearing. Coupled with the increasing population around the coastal areas, there is clearing of mangrove land for infrastructure development such as road and port construction. abrasion that occurs due to conversion and large-scale logging, both for the charcoal industry and firewood and scaffolding. Conclusion: Many factors influence the conversion of mangrove land along the coast of Indonesia, both in terms of economy, social and the environment of the local community. Social conditions of the community, low economic income of the community encourage economic activities of the community in addition to government policies suppressing land changes, thus affecting the increase in mangrove forest cover and deforestation and degradation of mangrove forests. In addition, the presence of strong natural factors allows some species to be unable to grow due to the conversion of nutrients, changes in substrate, changes in salinity or even high waves.